Reply to: A critical appraisal of the phylogenetic proposals for the South American Gomphotheriidae (Proboscidea: Mammalia) by M.A. Cozzuol, D. Mothé and L.S. Avilla - Alberdi, María Teresa (2012)
The objective of this paper is to reply the recent comments on our papers made by Cozzuol et al. (2011) about the phylogeny and biogeography of South American Gomphotheres. We addressed the methodological criticism and concluded that Sinomastodon is the sister group of the South American gomphotheres, as we originally proposed, despite the weighting scheme adopted to analyze the data. Therefore, we argue that our conclusions based on this phylogenetic hypothesis on the evolution and biogeography of this group is not properly refuted by Cozzoul et al. (2011).